Stock Valuation of Aviation Subsector Pre and Post-Pandemic COVID-19 - Andriani, Dwi; Martia, Dina Yeni; Fatimatuzzahro, Naila; Thoriq, Ziqri; Pinandhito, Kenneth (AFEBI Economic and Finance Review, 2024)
The study aims to assess the company's shares before, during, and after the COVID-19 pandemic by comparing the market price and the company's intrinsic value. The focus of the research is the intrinsic value of the company using the Price Earning Ratio (PER) and Price to Book Value (PBV) approaches, then compared to the market price so that it can find out the stock valuation to make investment decisions. The study analyzed the shares of the airline sector listed on the IDX from 2018 to 2022. The research sample is three companies selected using the purposive sampling technique. The three companies implement environmentally friendly aviation fuel (SAF) and have developed the intelligent airport concept for AP II since 2016. Data processing shows that before the pandemic (2018 - 2,019), the condition of aviation sub-sector stocks was worth buying because the market price was smaller than the intrinsic value. However, under the COVID-19 pandemic (2020 - 2021), the aviation sub-sector stocks are not recommended to be purchased because the market price is greater than the intrinsic value. After Covid 19 (2022), several aviation sub-sector stocks are worth buying, and one is less; therefore, the COVID-19 pandemic gave rise to a recommendation that aviation sub-sector stocks are worth buying because the operations of aviation companies are back to normal. Keywords: Covid 19; Intrinsic Value; Price Earning Ratio (PER); Price to Book Value (PBV)